OP58 Testing Of A Multiple Criteria Decision Analysis Value Framework With Decision Makers Across Europe. (2017) - Angelis, Aris; Linch, Mark; Montibeller, Gilberto; Molina-Lopez, Teresa; Zawada, Anna; Orze, Kinga; Arickx, Francis; Espín, Jaime; Kanavos, Panos
Abstract : INTRODUCTION: We test in practice a Multiple Criteria Decision Analysis (MCDA) framework for the value assessment of a set of therapeutic options for the indication of hormone relapsed metastatic prostate cancer (mPC) through a series of simulation exercises with the participation of decision makers from different Health Technology Assessment (HTA)/insurance agencies across Europe, including TLV (Sweden), AETSA (Andalusia-Spain), INAMI-RIZIV (Belgium) and AOTMiT (Poland). The drugs evaluated were abiraterone, cabazitaxel and enzalutamide. METHODS: Using a multi-attribute value theory framework, past research outcomes and literature findings, an mPC-specific value tree was constructed incorporating relevant concerns as criteria. By adopting the MACBETH approach the different drugs were scored against the criteria through the development of value functions, relative weights were assigned to the criteria using a swing weighting technique, scores and weights were combined using an additive aggregation technique, and sensitivity analysis of results was conducted. All stages were informed through the participation of a small group of experts from each HTA/insurance agency at a series of decision conferences taking place in each country. RESULTS: Value parameters considered spanned the dimensions of therapeutic impact, safety profile, innovation level and socioeconomic impact. Overall weighted preference value scores were produced reflecting the performance of the treatments against the criteria while considering their relative importance. Order of treatments' rankings was identical across all agencies, with enzalutamide scoring highest and cabazitaxel lowest. Therapeutic impact criteria always produced the greatest relative weight. Hypothetical priority setting decisions were made based on "value-for-money" grounds through the use of "cost per unit of value" metrics by incorporating purchasing costs. CONCLUSIONS: The MCDA framework tested possesses a number of characteristics that could facilitate decision making, including the systematic and explicit incorporation of value trade-offs as part of model assessment and the transparency throughout all its stages. Therefore, it has the prospects to act as a practical evaluation tool for value assessment and communication during the HTA process.